Mode I Stress Intensity Factors of Sickle-Shaped Surface Cracks in Round Bars - Ismail, Al Emran (International Journal of Integrated Engineering, 2016)
Nowadays, the sickle-shaped surface crack generally occurred around the bolt under tension due to the stress concentrations occurred at the design discontinuitiesThe behaviors of these cracks are not really understood and additionally it is hard to find the solutions of stress intensity factors of this kind of cracks. Therefore, the intention of this paper is to present the behavior of these cracks under tension loading. In order to understand the role of these cracks, there are seven crack aspect ratios, a/b are considered ranging from 0.0 to 1.2. For each crack aspect ratio, there are six relative crack depth, a/D are used ranging from 0.1 to 0.6. There are two types of loading are used so called free- and fix-stresses. ANSYS finite element program is used to model the crack. Stress intensity factor (SIF) which is based on the J-integral is used to characterize the cracks. For relatively shallow cracks (a/D â‰¤ 0.3), the role of SIFs along the crack front is insignificant where the values of SIFs remain flattened along the crack front as a/D increased. However, for the deeper cracks (a/D > 0.3), the effect of a/b is pronounced on the SIFs. If a/b is increased from 0.0 to 1.2, higher SIFs are obtained within the central compared with the outer regions. This is due to the fact that the circumferential crack at the both sides of the bar experienced lack of mode I opening mechanism compared with the crack faces of the upper side cracks. It is also found that the SIFs obtained under free tension stress is higher that the SIFs under fix stress due to the fact that free stress condition capable to induce the bending moment effect and therefore widening the crack faces.